An interactive platform for online learning using RoR / Nor Nadiha Nor Din - Nor Din, Nor Nadiha (2019)
This project is about an interactive online platform for online tutoring using gamification features. Gamification is use in the online learning to attract the users and increase the user’s motivation and performance. Using gamification, we will create a clear learning pathway so that the users know what level they need to complete to move on to the level. Apart from that, the implement of badges will keep the learners returning to avoid breaking their achievement. Moreover, matchmaking system connects multiple users to participate in online learning. Using this method, users can interact with each other such as sharing the knowledge and notes from all over the world or even communicate with other users in the same system. This project use Ruby on Rails framework as Ruby on Rails is a well known framework use in developing web application. This framework also is very easy to use because it is very flexible language. The methodology used to develop the system is Web Development Life Cycle (WDLC) because the methodology is suitable to develop web-based system quickly in a structured manner. At the end of this project, users can use the system to choose the subject they want to learn and teach and they can use the gamification system to complete an assessment given.